Crashworthiness behaviour of the stiffened panel in idealized penetration test: A developed stiffening configuration against impact loading - Brilliant Aditya Fhandy; Aditya Rio Prabowo; Tuswan Tuswan; Achmad Zubaydi; Dharu Feby Smaradhana; Seung Jun Baek; Siti Nurlita Fitri (Brodogradnja)
This study focuses on the crashworthiness performance due to collision accidents on stiffened plate panels on ship structures. Numerical impact simulation using explicit dynamic with ANSYS software on the stiffened plate with quasi-static loading is investigated. The investigation emphasizes numerical parameters such as mesh size and geometric parameters, including stiffener type, spacing, and configuration. Benchmarking results show high accuracy, with force-displacement trends and fracture energy discrepancies less than 5 % compared to experimental data. Deformation and fracture contours are similar to experimental observations, particularly at plate-stiffener intersections. Key findings highlight the crucial impact of mesh size on accuracy, where a finer mesh size significantly increases the accuracy level. The study also evaluates the effect of different stiffener types, configurations, and spacings on crashworthiness. The Single-L and Cross-Y stiffeners perform better than the T and I stiffeners. Other investigations show stiffener configuration and stiffener spacing generally influence crashworthiness performance. This research underlines the importance of detailed structural analysis for enhancing ship safety in collision scenarios, vital for minimizing potential losses and environmental damage.